Exploring the metabolic potential of microbial communities in ultra‐basic, reducing springs at The Cedars, CA, USA: Experimental evidence of microbial methanogenesis and heterotrophic acetogenesis. Issue 4 (29th April 2016) - Kohl, Lukas; Cumming, Emily; Cox, Alison; Rietze, Amanda; Morrissey, Liam; Lang, Susan Q.; Richter, Andreas; Suzuki, Shino; Nealson, Kenneth H.; Morrill, Penny L.
Abstract: Present‐day serpentinization generates groundwaters with conditions (pH > 11, Eh < −550 mV) favorable for the microbial and abiotic production of organic compounds from inorganic precursors. Elevated concentrations of methane, C2 ‐C6 alkanes, acetate, and formate have been detected at these sites, but the microbial or abiotic origin of these compounds remains unclear. While geochemical data indicate that methane at most sites of present‐day serpentinization is abiogenic, the stable carbon, hydrogen, and clumped isotope data as well as the hydrocarbon gas composition from The Cedars, CA, USA, are consistent with a microbial origin for methane. However, there is no direct evidence of methanogenesis at this site of serpentinization. We report on laboratory experiments in which the microbial communities in fluids and sediments from The Cedars were incubated with 13 C labeled substrates. Increasing methane concentrations and the incorporation of 13 C into methane in live experiments, but not in killed controls, demonstrated that methanogens converted methanol, formate, acetate (methyl group), and bicarbonate to methane. The apparent fractionation between methane and potential substrates ( α 13 CCH4‐CO2(g)  = 1.059 to 1.105, α 13 CCH4‐acetate  = 1.042 to 1.119) indicated that methanogenesis was dominated by the carbonate reduction pathway. Increasing concentrations of volatile organic acid anions indicated microbial acetogenesis. α 13 CCO2(g)‐acetate values (0.999 to 1.000), however, were inconsistent with autotrophic acetogenesis, thus suggesting that acetate was produced through fermentation. This is the first study to show direct evidence of microbial methanogenesis and acetogenesis by the native microbial community at a site of present‐day serpentinization. Key Points: Evidence for methanogenesis and acetogenesis by microbial communities in serpentinization springs Autotrophic (dominant) and heterotrophic methanogenesis and heterotrophic acetogenesis detected We provide apparent fractionation factors relevant for future field studies